Research on the Temporal and Spatial Evolution Characteristics of Evapotranspiration and Its Components of Guangdong Province Based on GLEAM Dataset in the Past 30 Years - WANG Dayang (Renmin Zhujiang)
Based on the remote sensing evapotranspiration dataset of GLEAM,this paper analyzes the temporal and spatial evolution characteristics of evapotranspiration and its components from 1989 to 2018 in Guangdong province,studies the temporal and spatial changes of evapotranspiration in the past 30 years by combining the Mann-Kendall and Sen's slope,and discusses the temporal and spatial evolution trends and patterns of components such as vegetation transpiration,soil evaporation and interception loss,and analyzes the cause of the change in evapotranspiration based on the normalized difference vegetation index (NDVI) of Guangdong province.The research can provide a scientific reference for thorough understanding of surface hydrological processes and energy balance processes under the condition of climate change.